Public affairs in practice : a practical guide to lobbying - Thomson, Stuart, 1972- (PR in practice series., 2007)
Public affairs today is more than just political lobbying. It requires working with other policy-making bodies, such as regulators, commercial organizations and other interested parties. ''Public Affairs in Practice'' is the first book to examine the methods public affairs professionals use to make an impact. It covers each aspect of the industry and examines the tools needed to deliver an effective public affairs program. It also highlights the potential benefits of public affairs, including protection from perceived threats of new regulation, identifying new market opportunities and raising.